PENGARUH KEMAMPUAN KERJA DISIPLIN KERJA DAN PEMBERIAN REWARD TERHADAP KINERJA PEGAWAI DI BADAN PENGELOLAAN KEUANGAN DAN PENDAPATAN DAERAH KABUPATEN BULELENG - Kartika, Riana Dewi; Nanda, Nyoman Chandrika (Jurnal Daya Saing, 2024)
This study aims to determine the Influence of Work Ability, Work Discipline and RewardGiving on Employee Performance at the Regional Financial and Revenue Management Agency ofBuleleng Regency. The population of employees of the Buleleng Regency Regional Financial andRevenue Management Agency is 338 employees and the number of samples in this study is 77 peoplecalculated by the slovin formula. The data analysis techniques used in this study are validity andreliability test, classical assumption test, multiple linear regression analysis and t-test using the SPSSversion 18 application for windows.The results of this study show that work ability affects the performance of employees at the RegionalFinancial and Revenue Management Agency of Buleleng Regency by 0.179. The results of hypothesistesting with the T-Test test found that the t-test > t-table (5,155 > 1,668). This shows that work abilityhas a positive and significant effect on employee performance seen from a significant level of 0.000 <0.05. Work discipline affects the performance of employees at the Buleleng Regency RegionalFinancial and Revenue Management Agency by 0.190. The results of hypothesis testing with the TTest test found that the t-test > t-table (5,339 > 1,668). This shows that work discipline has a positiveand significant effect on employee performance seen from a significant level of 0.000 < 0.05. Theprovision of rewards affects the performance of employees at the Regional Financial and RevenueManagement Agency of Buleleng Regency by 0.118. The results of hypothesis testing with the T-Testtest found that the t-test > t-table (2,592 > 1,668). This shows that the provision of rewards has apositive and significant effect on employee performance seen from a significant level of 0.012 < 0.05.